(untitled) (Journal of Asian Development Studies, 2025)
South Asia relies considerably on foreign aid to ameliorate its economic development. The primary cause of this reliance on foreign aid is a lack of resources to enhance macroeconomic performance. This study investigated how foreign aid affects South Asia’s macroeconomic performance. Additionally, the significance of financial development is emphasized to assess the aid growth relationship. The panel autoregressive distributed lag (P-ARDL) model is part of an advanced panel data method. The study concluded that foreign aid does not enhance South Asia’s macroeconomic performance; however, it does have a favourable and noteworthy effect on economic growth related to financial development. Therefore, it is argued that a well-developed financial system can accelerate the effectiveness of foreign aid in South Asia.